Promoting mitochondrial fusion is protective against cancer-induced muscle detriments in males and females - Francielly Morena; Seongkyun Lim; Ana Regina Cabrera; Toby L. Chambers; Pieter J. Koopmans; Stavroula Tsitkanou; Sabin Khadgi; Calvin Peterson; Eleanor R. Schrems; Ruqaiza Muhyudin; Sepideh Shakeri; Kevin Zhao; et al. (BMC Cancer)
Abstract Background Skeletal muscle atrophy during cancer-induced cachexia remains a significant challenge in cancer management. Mitochondrial defects precede muscle mass and functional losses in models of cancer cachexia (CC). We hypothesized targeting Opa1—a key regulator of mitochondrial fusion—can attenuate LLC-induced CC outcomes. Methods We utilized 1) in vivo transgenic Opa1 overexpression (OPA1 TG) in LLC-induced CC in vivo, and 2) BPG15 administration to induce Opa1 in vitro and in vivo. Results OPA1 TG attenuated plantaris, gastrocnemius, and EDL loss with LLC in males and alleviated gastrocnemius loss in females. OPA1 TG had greater mitochondrial respiration in plantaris and white gastrocnemius, and lowered pMitoTimer Red Puncta (-63%), a proxy for mitophagy in males. OPA1 TG protected muscle contractility at physiological stimulation frequencies by up to 60% in female LLC mice. OPA1 TG enhanced the ratio of OPA1/DRP1 protein content—a proxy for fusion and fission balance—in males and females. In vitro, BGP-15 attenuated LLC conditioned media-induced myotube atrophy by ~ 9% concomitant with suppression of the transcriptional factor FoxO3, autophagy markers, and inflammatory cytokines. In vivo, BGP-15 improved contractility at lower frequencies (10-60 Hz), with LLC-BGP-15 showing up to 20% greater torque than LLC-control. BGP-15 treated LLC animals had 71% fewer pMitoTimer red puncta, suggesting attenuated mitophagy. Conclusions Promoting mitochondrial fusion via OPA1 induction improved cachectic outcomes in mice. Targeting OPA1providing provides a promising therapeutic approach for CC treatment. Graphical Abstract Mitochondrial dynamics are disrupted in skeletal muscle during cancer cachexia (CC), with reduced fusion and increased fission contributing to mitochondrial and muscle dysfunction. OPA1, a key protein regulating mitochondrial fusion, is downregulated in male mice at early stages of CC in the Lewis Lung Carcinoma (LLC) model. To restore balance, we employed two strategies: (1) transgenic overexpression of Opa1 and (2) pharmacological induction of OPA1 using BGP-15 in vitro and in vivo. In vitro, BGP-15 treatment improved myotube size while modulating key autophagy-related markers, such as Foxo3 and Atg7. In vivo, both approaches alleviated cachectic outcomes in LLC-bearing mice by enhancing muscle mass, contractile function, and mitochondrial respiration. These findings underscore the therapeutic potential of OPA1 induction in mitigating skeletal muscle atrophy and dysfunction during CC. Our results highlight OPA1 as a promising target to restore mitochondrial homeostasis and improve muscle outcomes in both male and female cachexia models.